Nigella Sativa (Black Seed) Medical Properties - Тuychiyev G’afurjon O’rmonovich; Rustamov Xondamir Kamol o’g’li (Scientific Trends, 2025)
Nigella sativa, commonly called black seed, black cumin, or kalonji, is an annual herb of the Ranunculaceae family widely used in traditional medicine across Asia, the Middle East, and parts of Europe. Its seeds and derived oil contain multiple bioactive compounds, especially thymoquinone, with potential antioxidant, anti-inflammatory, antimicrobial, anticancer, hypoglycemic, hypolipidemic, and immunomodulatory effects. This review summarizes up-to-date evidence on its phytochemical profile, mechanisms of action, outcomes in preclinical and clinical studies, and safety considerations. It also highlights gaps in knowledge and suggests directions for future research.
Keywords: Nigella sativa; kalonji; black seed; thymoquinone; antioxidant; immunomodulation; clinical trials.